(untitled) (Proceedings of Voronezh State University. Series: Geology, 2021)
Introduction: Earlier results of petrological and mineralogical studies of xenoliths in garnetiferous trondhjemites from the Central Zone of the Lapland Granulite Belt in the area of the Lotta river were used to model their mineral associations by means of the pseudo-cut method. Methodology: The calculations of P-T parameters and fluid evolution during metamorphism were conducted by using the well-proven GEOPATH, TWQ, PERPLEX software systems based on mutually agreed thermodynamic data bases. The compositions of the minerals were determined by a CamScan MV2300 (VEGA TS 5130MM) electron microscope with a Link INCA Energy energy dispersive analysis system. Fluid inclusions in metamorphic rocks were studied in plates 200-300 μm thick, polished on both sides, using a Linkam system with an operational temperature range from -196°C to 600°C (THMSG 600) and automatic modes of sample heating and cooling at a rate of 0.1 to 90°/min Results and discussion: 1. Modelling of mineral associations of xenoliths by the pseudo-cut method and thermobarometry: the calculated P-T pseudo-cuts in the range of 5-9 kbar and 600-800°C are represented by simple diagrams dominated by the field of Opx+Cpx+Pl+Qz+Ilm association. Using the winTWQ_2.32 software package Cpx+Opx, equilibrium temperatures were calculated for 59 pairs of minerals. The am-phibole-plagioclase equilibrium was used to simulate the amphibolisation process which recorded the temperatures of xenolith amphibolisation of 740-780°C at a pressure of 5.0-5.5 kbar. 2. Fluid inclusions: fluid inclusions were studied in quartz and presented by carbon-dioxide and water-salt varieties. Conclusions: Xenolith amphibolisation is associated with the penetration of substantially aqueous fluid from the cooling trondhjemite magma. This is proved by an evident predominance of water-salt (17-20 wt. % of NaCl equivalent) and subordinate quantity of carbon dioxide inclusions in granitoid minerals. Despite active fluidic interaction between the melt and xenoliths, no signs of thermal effect were established.